Market time-series reversal: evidence from China’s market - Xiang, Yun; Luo, Longang; Yu, Xisheng (Technological and Economic Development of Economy, 2025)
Upon high-frequency data of China Securities Index 300 (CSI 300) exchange-traded fund and index future contracts, we demonstrate a time-series reversal pattern between the last three-hour returns on current day and those on previous day. Further this reversal is also found in China index future market. This predictability has been illustrated to be both statistically and economically significant, and the significance is stronger on more volatile/higher volume days and non-bearish market state. Extensive regression analysis suggests that the time-series reversal is mainly induced by irrational investor overreaction, not by the lack of liquidity provision. Moreover, the economic value of the reversal pattern is evaluated to yield an outstanding trading performance by executing a market timing strategy. First published online 02 April 2025